Sustainable financing and community resource management - Garcia, Michael Lyndon B. (2003)
his paper explores the relationship between sustainable financing and community resource management (CRM). It argues that many CRM programs in the Philippines today have been infused with sustainability principles through approaches that ensure people's participation and involvement. These approaches include community organizing, education, training and advocacy, sustainable livelihoods and sustainable financing. All these are meant to develop and enhance local capacities, thus, promoting local-level management of community resources. However, it is noted that among these strategies, sustainable financing remains problematic as most CRM programs in the country remains dependent on external funding supports. This paper argues that CRM programs in the country should develop sustainable financing mechanisms to reduce reliance on donor funding thereby making these programs truly sustainable.
Keywords: Community based resource management